Obtención de biocombustible sólido a partir de residuos de frutas - Lopez Del Rio, Jhofre Pablo (2021)
The main objective of this work was: to obtain solid biofuel from fruit residues, in order to take advantage and be used later in heating systems. The work carried out has a quantitative approach with a descriptive correlational depth level. The study population was the fruit residues from the markets of Bethlehem, central market and model market, the type of sampling is probabilistic at the discretion of the researchers, considering the sample size a maximum of 1k, 500 grams (500 gr Nativity market, 500 gr. Central market and 500 gr. Model market). The sources from which the data were obtained such as: data collection, weighing, humidity, ash, grinding, sieving, obtaining pellets and calorific value, were undergraduate and postgraduate theses as well as an internet source. The results obtained from the 3 samples analyzed, from the Bethlehem, Central and Model markets resulted in a high calorific value M1:9549.74 kcal / kg, M2: 95551.36 kcal / kg, M3: 9671.36 kcal / kg, M4: 9483, 4 kcal / kg which correspond to 4 samples produced respectively. In conclusion, it was shown that a biofuel can be obtained with optimal energy combustion with fruit residues.